Guidelines for creation of a Luk Thung method for trumpet - Suwantada, Patcharee; Bowman, Joseph (Malaysian Journal of Music, 2022)
21st century trumpet players are required to play many diverse styles of music. One of these unique musical styles, Luk Thung (a Thai traditional music style) is music derived from Thai folk music culture that describes the Thai rural lifestyle, especially in the lyrics. Learning this style is a crucial part of a trumpet player’s chances for career success in Thailand’s musical industry. For trumpet players, performing Luk Thung music requires fundamental trumpet techniques. Because of the need for training trumpet players in this unique Thai musical style, this research aims to generate the guidelines for a trumpet method design based on Luk Thung music through the study of three categories: (1) fundamental trumpet techniques appearing in Thai Luk Thung music; (2) comparison of fundamental technique approaches between Western pedagogical methods for trumpet and Luk Thung music; and (3) the possibility of using Thai Luk Thung music to develop fundamental trumpet techniques for trumpet players. The purposeful sampling includes official recordings of Thai Luk Thung songs, four major method books for trumpet and in-depth interviews used for collecting data, and analysis. The findings were discussed and presented as the guidelines to design a trumpet method including purpose of the method design, structure of the method, and scope of contents. The generated guidelines will help trumpet players, music teachers or trumpet educators to design their own trumpet methods based on Thai Luk Thung music that suits their needs.